Analisis SWOT sebagai Strategi Peningkatan Pengunjung Eduwisata Garam Madura - Hikma Sofia; Miftahul Jannah; Vidi Hadyarti (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to determine the potential and problems experienced by Eduwisata Garam Madura. These potentials and problems can be analyzed using a SWOT analysis. from the analysis, it can be found strategies that can be applied in Eduwisata Garam Madura. Strategies that can be applied include utilizing the concept of edutourism by making the destination attractive to visit and providing river crossing facilities and adding instagramable selfie spots so that consumers are loyal, utilizing the e-salt concept by providing affordable prices to attract the attention of new visitors, and completing area facilities. ample parking and transportation to minimize customers switching to new competitors and visitors can visit Eduwisata Garam Madura.